The Effect of Relevant Costs on the Income of Traditional Cake Traders with Local Wisdom Mopo'o Tanggalo Duhelo as a Moderation Variable - Shalwa Mustafa; Tri Handayani Amaliah; Ayu Rakhma Wuryandini (Economics and Digital Business Review, 2026)
This study aims to analyze the influence of relevant costs on the income of traditional cake traders with the local wisdom of Mopo'o Tanggalo Duhelo as a moderation variable in traditional cake traders in the Moodu Traditional Market, Gorontalo City. The research uses a quantitative method with an associative approach. Data was obtained through the distribution of questionnaires to 30 respondents who were selected using saturated sampling techniques. Data analysis was carried out by simple linear regression and Moderated Regression Analysis (MRA) using the help of the SPSS program. The results of the study show that relevant costs have a positive and significant effect on the income of traditional cake traders with a contribution of 17.1%. This influence is reflected in the dominance of indicators of the decision to continue or stop the business, which shows that traders consider costs and profits in determining the sustainability of their business. In contrast, the indicator of the decision to sell or further process has the lowest contribution because some traders have not fully considered the additional costs and economic benefits in decision-making. The results of the study also showed that the local wisdom of Mopo'o Tanggalo Duhelo was able to strengthen the relationship between relevant costs and traders' income. The indicator of trading honesty was the most dominant aspect of moderation, while patience in the face of risk was the indicator with the lowest contribution. The Mopo'o Tanggalo Duhelo variable is classified as a quasi moderator.